Power plays politics, football, and other blood sports - Barry, John M., 1947- (Jackson University Press of Mississippi, 2001)
Barry, a former Washington journalist and college football coach, compares the abuse of power in politics and sports.
Includes index.
Donated by Logan Wangsgard (Hall's Book Drive) Dec. 2015.
Keywords: Power (Social sciences) -- United States -- History -- 20th century; Political corrupti -- United States -- History -- 20th century; Football -- Social aspects -- United States -- History -- 20th century; Sports -- Social aspects -- United States -- History -- 20th century; Politicians -- United States -- Biography; Athletes -- United States -- Biography; United States -- Politics and government-1989-.